Poor Performance in Grade 9 Mathematics: Students’ Attributions - Saeedullah (JSE, 2023)
Abstract The present study investigated secondary school students’ views about their poor performance in the subject of mathematics in Lahore. The study was descriptive in nature and survey research design with a qualitative approach was used. The researcher developed an open-ended questionnaire and purposively selected 40 participants (20 boys and 20 girls) from 10 secondary schools to collect the data.